Phenotypes, Genotypes, and Treatment Options of Primary Failure of Eruption: A Narrative Review - Luca Testarelli; Francesca Sestito; Adriana De Stefano; Chiara Seracchiani; Roberto Vernucci; Gabriella Galluccio (MDPI AG, 2022)
Tooth eruption is a complex process, during which a series of factors can cause a failure of it. Among this, primary failure of eruption (PFE) is a non-syndromic condition that leads to an incomplete tooth eruption despite the presence of a clear eruption pathway. The aim of this narrative review is to provide an overall view about clinical considerations, genetics-related aspects, and possible treatments of PFE based on the latest findings. A literature search using the PubMed/Medline and Scopus database was performed. The search terms used were "PFE", "orthodontics", "primary failure of eruption", and "treatment", and all the articles, according to the inclusion criteria, from 2008 until June 2022 were screened. Among them, 12 articles were considered useful to highlight some of the main genotypical and phenotypical aspects and several treatment options. Indeed, if there is a suspicion of primary failure of eruption, a PTH1R screening should be performed, because a mutation in this gene is responsible for an altered balance between the resorptive and the appositional processes during the eruption. This is important to know before starting an orthodontic treatment because it could lead to ankylosis of the affected tooth, exposing patients to iatrogenic damage. Treatment options depend on the growth phase of the patient and on the clinical situation.